(6.1) Find det(C) if (1) C = λ λ + 1 λ λ − 1 (6.2) Use the cofactor expansion to determine 2 0 0 0 3 1 2 0 2 −5 0 4 1 3 0 3 (6.3) Consider the matrix A = 1 4 2 3 (a) Compute A −1 (b) Find det(A **−1 ) (c) Deduce a relation (if it exists) between det(A) and det(A **−1
6.1.
"C=\\begin{bmatrix}\n\n \\lambda& \\lambda+1\\\\\n\n \\lambda& \\lambda-1\n\n \\end{bmatrix}"
"Det(C)=\\begin{vmatrix}\n\n \\lambda& \\lambda+1\\\\\n\n \\lambda& \\lambda-1\n\n \\end{vmatrix}"
"=\\lambda(\\lambda-1)-\\lambda(\\lambda+1)\n\n =-2\\lambda"
6.2
The given determinant is "\\begin{vmatrix}\n\n 2&0&0&0\\\\\n\n 3&1&2&0\\\\\n\n 2&-5&0&4\\\\\n\n 1&3&0&3\n\n \\end{vmatrix}"
Use the cofactor expansion corresponding to the first row.
"=2 \\begin{vmatrix}\n\n 1&2&0\\\\\n\n -5&0&4\\\\\n\n 3&0&3\n\n \n\n \\end{vmatrix} -0+0-0"
"=2 \\begin{vmatrix}\n\n 1&2&0\\\\\n\n -5&0&4\\\\\n\n 3&0&3\n\n \n\n \\end{vmatrix} \n\n\n\n =2[1(0-0)-2(-15-12)+0]\n\n =2[54]=108"
6.3
"(a) \\text{The given matrix is-\n}\nA=\\begin{bmatrix}\n\n 1&4\\\\\n\n2&3\\end{bmatrix}"
"det A=\\begin{vmatrix}\n\n 1&4\\\\\n\n2&3\\end{vmatrix}=3-8=-5"
"det A=-5 \\neq 0."
"\\Rightarrow A^{-1}" exist.
Now, "adj.(A)=\\begin{bmatrix}\n\n 3&-2\\\\\n\n2&3\\end{bmatrix}^T\n\n\n\n\\Rightarrow adj(A)=\\begin{bmatrix}\n\n 3&-4\\\\\n\n-2&1\\end{bmatrix}"
So, "A^{-1} =\\dfrac{adj A}{det (A)}=\\dfrac{1}{-5}\\begin{bmatrix}\n\n 3&-4\\\\\n\n-2&1\\end{bmatrix}=\\begin{bmatrix}\n\n \\dfrac{-3}{5} & \\dfrac{4}{5}\\\\\\\\\n\n\\dfrac{2}{5} & \\dfrac{-1}{5}\\end{bmatrix}"
(b)
"det(A^{-1})=\\begin{vmatrix}\n\n \\dfrac{-3}{5} & \\dfrac{4}{5}\\\\\\\\\n\n\\dfrac{2}{5} & \\dfrac{-1}{5}\\end{vmatrix}"
"=\\dfrac{3}{25}-\\dfrac{8}{25}=\\dfrac{3-8}{25}=\\dfrac{-5}{25}=\\dfrac{-1}{5}"
(c) We have, "det(A)=-5 \\text{ and }det(A^{-1})=\\dfrac{-1}{5}"
"det(A).det(A^{-1})=(-5).(-\\dfrac{1}{5})=1"
Hence "det(A).det(A^{-1})=1"
This is the required relation.
Comments
Dear prince, the answer to question 6.2 is correct.
question 6.2 the answer is -108 2(1)((54)(-1)) = 2(54(-1)) = -108
Leave a comment